Vietnamese Women’s Representation in TV Commercials Related to Lunar New Year: A Critical Discourse Analysis - Lien, Nguyen Hong (VNU Journal of Foreign Studies; Vol 32 No 2, 2016)
Abstract: This research is placed within the critical discourse analysis perspective that assumes an entangled relationship between discourse and its underlying social meanings. Explicitly, the study of Vietnamese women's representation in 25 TV advertisements related to Lunar New Year with emphasis on gender roles has been conducted. The study, which is expected to fill the present gap, seeks an answer to how Vietnamese women are characterized in TV commercials and whether this reflection sustains or challenges the existing ideologies in the current society. Employing the framework of Fairclough (1989), Halliday (2014) and Kress and van Leeuwen (2006), the research has reached the following findings: (1) laid in the domestic landscape, Vietnamese women are simultaneously portrayed as different characters; (2) the existing gender ideologies of Confucian ethics upon women can be said to be still upheld; and (3) there seems to be no opposition to the current belief. Keywords : Critical discourse analysis, TV advertisements, women's representation, gender ideologies.